ChemInform Abstract: Mechanistic Insights into a Catalyst‐Free Method to Construct Quinazolinones Through Multiple Oxidative Cyclization. Issue 25 (June 2016) - Wang, Zhen‐zhen; Tang, Yu
Abstract: An oxidative cyclization of 2‐aminobenzamides with benzylic alcohols is developed to give varying yields of 2‐acylated quinazolinones in the presence of elemental oxygen as terminal oxidant.